New species in the Tricholoma pardinum complex from Eastern Himalaya - Yang, Zhu L.; Ding, Xiao-Xia; Kost, G.; Rexer, K.-H. (Phytotaxa, 2017)
Species of Tricholoma sect. Pardinicutis (Singer) Bon are relatively easily recognizable even in the field, and the type species of section, T. pardinum (Pers.) Quél., was reported from the eastern Himalaya and adjacent areas. However, such reports were largely based on superficially similar morphology. In this study, we have generated DNA sequences of samples from southwestern China, and found that there are molecular discrepancies between the Chinese collections and European ones. Further detailed morphological analyses indicated the two independent new species occur in southwestern China, one in subtropical coniferous forests mixed with fagaceous plants between 2400 and 2800 m altitude, the other in subalpine dark coniferous forests between 3300 and 4100 m altitude. Consequently, two new species, namely, T. highlandense and T. sinopardinum, are described and illustrated.